Pengaruh Flash Sale dan Live Streaming Terhadap Impulse Buying pada Konsumen Penginapan Murah Malang - Qarina Chuzaimah Al – Hilaliyah; Sanita Dhakirah; Mohammad Maskan (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The rapid advancement of digital technology has transformed consumer behavior, particularly by increasing the prevalence of impulsive buying through social media platforms such as TikTok. Flash sales and live streaming have become common strategies adopted by businesses, including Penginapan Murah Malang through its TikTok account @penginapanmurahmalang. However, the implementation of these strategies has not been followed by optimal results, as indicated by a decline in guest occupancy rates from a peak of 19% in August 2025 to 10% in December 2025. This study aims to examine the effect of flash sales and live streaming on impulsive buying behavior among consumers of Penginapan Murah Malang. A quantitative descriptive approach was employed, involving 100 respondents selected using purposive sampling, namely those who had watched the account's live streaming sessions and had made a booking. Data were analyzed using multiple linear regression, accompanied by validity, reliability, and classical assumption tests, as well as t-tests and F-tests. The results show that flash sales and live streaming have a positive and statistically significant effect on impulsive buying, both partially and simultaneously, with the two variables contributing an (Adjusted R²) of 0.386. Live streaming was found to have a more dominant influence than flash sales. Based on these findings, it is recommended to increase the frequency of flash sales and strengthen consumer trust in streamers in order to optimize consumers' impulsive buying behavior